PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR - Meimi Elson (DIADIK, 2024)
This research purposes : (1) To improve the working attitude of class X SMK 01 Mukomuko. (2) To improve students' skills install electrical installation method approach demonstration. (3) To determine whether the approach demonstration method can improve the working attitude and skills to install electrical installations student. The learning method used in this research is the method of demonstration. Type of research is the Classroom Action Research (Classroom Action Research), which was conducted during three cycles. The test objective of the research is instrument used in the form of pre-test and post-test, the observation sheet the ability of teachers in the application of methods of demonstration, observation sheet of students' work attitudes in installing electrical installations and observation sheet of students to the skills in installing electrical installations. The analysis of the data was performed using the of t test tests to compare the differences in the skills of each cycle and between cycles. Subjects in this study are students of class X Skill Competency Power Installation Engineering (TITL) SMK Negeri 01 Mukomuko Academic Year 2015/2016, amounting to 18 students. The results showed an increase in value - average skills of students in each cycle the action. Besides the increased ability and the preparation of teachers in teaching materials using the method of demonstration also improve the working attitude in installing electrical installations. It can be concluded that the application of the method of demonstration to improve work attitude and skills to install electrical installations. This study also produced an instructional method demostration it consist generic, meaning that this demonstration and able to apply in other subject have is with the class of PTK in this study